Prevalencia de hemiltos enteroparasitos zoonoticos y factores asociados en Caninos domésticos (canis familiaris) en el barrio San Pedro de tenería parroquia de Pastocalle. - Chango Toalombo, Verónica Mercedes (2018)
The investigation of the present project has been carried out in the San Pedro neighborhood of Pastocalle Parish, in order to establish the prevalence of zoonotic enteroparasitic helminths in domestic canines, the scientific information was extracted from authors and specialized sources, as a primary part was applied a survey of the owners of the canines and the collection of fecal samples from the animals was carried out in a technical manner following the protocols for later analysis in the laboratory For the fecal samples collection, 75 canines were taken at random, after being processed and analyzed, a statistical table is issued which details the type of parasite found to define the level of infection of the animal, with this data it will be possible to establish the risk factors of domestic dogs (canis familiaris) and to which people are exposed to live with the sick animal. The level of involvement in the organism of human beings and the consequences of acquiring a parasitic infection from diseased canines can be determined and the results can be socialized. obtained to the population that was the subject of study. Through field research in the application of the surveys it was possible to observe directly the living conditions of the dogs and the way in which the owners take care of their pets, as regards deworming, visits to the veterinarian to supply the vaccines that are mandatory, with this has been determined what may be the associated factors that can generate risks in the coexistence between humans and pets, with them it was possible to provide a scientific and technical contribution to the owners of the canines which should be made aware in improve the living conditions of the animal for mutual benefit.